WAHDAT AL WUJUD DALAM PEMIKIRAN IBNU ARABI - Rofi'ie, Abd Halim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Ibnu Arabi, the Grand Master of Islam, is a great thinker whose controversial thought, wahdat al-wujud, has significantly influenced the mystiques of Islam. The meaning of wahdat al-wujud is basically two folds, i.e. that Being is the only One which exists and that the universe is merely a manifestation of the One. The One Being here refers to Allah SWT. The One covers up all the existing phenomena and functions as a resource which emanates the entire universe. In this context, He is referred to as al-Haqiqat al-Muhammadiyah. He might also be viewed as both the Universal Soul for His being the source of cosmos that governs the universe and the Universal Body for His reflecting any actions on every single micro existence that forms the universe. Furthermore, when His existence is deemed as a jauhar (jewel) that face-up any occurrences, He is typically known as al-haba’. The concept of wahdat al-wujud can actually be simplified into the principle of laa maujuda illa wujud al-wahid (no existence except the Existing One, the Being). The One might reveal His own existence into different martabat or levels: Martabat Ahadiyah, Martabat Wahidiyah, and Martabat Tajalli Syuhudi. Those standing points trigger Ibnu Arabi to believe that any kinds of realities or existences are nothing but a true reflection of the One.